Low pH Attenuates Apoptosis by Suppressing the Volume-Sensitive Outwardly Rectifying (VSOR) Chloride Current in Chondrocytes - Kittl, Michael; Winklmayr, Martina; Preishuber-Pflügl, Julia; Strobl, Victoria; Gaisberger, Martin; Ritter, Markus; Jakab, Martin (Frontiers in Cell and Developmental Biology, 2022)
In a variety of physiological and pathophysiological conditions, cells are exposed to acidic environments. Severe synovial fluid acidification also occurs in a progressive state of osteoarthritis (OA) affecting articular chondrocytes. In prior studies extracellular acidification has been shown to protect cells from apoptosis but the underlying mechanisms remain elusive. In the present study, we demonstrate that the inhibition of Cl- currents plays a significant role in the antiapoptotic effect of acidification in human articular chondrocytes. Drug-induced apoptosis was analyzed after exposure to staurosporine by caspase 3/7 activity and by annexin-V/7-actinomycin D (7-AAD) staining, followed by flow cytometry. Cell viability was assessed by resazurin, CellTiter-Glo and CellTiter-Fluor assays. Cl- currents and the mean cell volume were determined using the whole cell patch clamp technique and the Coulter method, respectively. The results reveal that in C28/I2 cells extracellular acidification decreases caspase 3/7 activity, enhances cell viability following staurosporine treatment and gradually deactivates the volume-sensitive outwardly rectifying (VSOR) Cl- current. Furthermore, the regulatory volume decrease (RVD) as well as the apoptotic volume decrease (ADV), which represents an early event during apoptosis, were absent under acidic conditions after hypotonicity-induced cell swelling and staurosporine-induced apoptosis, respectively. Like acidosis, the VSOR Cl- current inhibitor DIDS rescued chondrocytes from apoptotic cell death and suppressed AVD after induction of apoptosis with staurosporine. Similar to acidosis and DIDS, the VSOR channel blockers NPPB, niflumic acid (NFA) and DCPIB attenuated the staurosporine-induced AVD. NPPB and NFA also suppressed staurosporine-induced caspase 3/7 activation, while DCPIB and Tamoxifen showed cytotoxic effects per se. From these data, we conclude that the deactivation of VSOR Cl- currents impairs cell volume regulation under acidic conditions, which is likely to play an important role in the survivability of human articular chondrocytes.